2011
DOI: 10.3945/ajcn.111.012278
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc concentration responds to short-term zinc supplementation, but not zinc fortification, in young children in Senegal

Abstract: Plasma zinc concentration increased in children who received daily zinc supplementation for 15 d but not in those who received a zinc-fortified complementary food containing a similar amount of zinc. Additional longer-term studies are needed to assess the effect of zinc-fortification programs on zinc-related functional outcomes and the usefulness of plasma zinc as a biomarker of program effect. This trial was registered at www.clinicaltrials.gov as study NCT0094398.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Similar findings have been described by Lo et al [41] who found that plasma zinc concentration increased in children who received daily zinc supplementation for but not in those who received zinc with complementary foods suggesting the role of inhibitors in absorption.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have been described by Lo et al [41] who found that plasma zinc concentration increased in children who received daily zinc supplementation for but not in those who received zinc with complementary foods suggesting the role of inhibitors in absorption.…”
Section: Discussionsupporting
confidence: 89%
“…In total, we identified 24 studies [48,57,70,71,73,74,75,76,77,79,82,85,87,88,89,90,91,93,97,98,99,100,101,102,103], with 33 comparisons, meeting our inclusion criteria and reporting on the impact of zinc on diarrhea, respiratory infections and fever. Twenty-one studies were individually randomized and three studies cluster randomized trials.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies [48,57,70,75,82,85,87,88,91,97,99,100,102,103,104,105] reporting on fever and/or respiratory infections, only 3 [82,91,104] found a positive effect of zinc intake. Out of the 24 studies investigating the effect of zinc on diarrhea, 11 studies [48,57,70,74,75,76,79,85,87,88,99] found no effect at all. Ten [71,73,89,90,91,93,97,100,101,102] reported a positive effect of zinc use on the prevalence and or incidence of diarrhea.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of change in plasma zinc concentrations with ASFs may be because the additional absorbed zinc was deposited in tissues rather than remaining in circulation (38). Others have reported that 3.5 mg Zn/d provided as a fortified porridge had no impact on the plasma zinc status in children, but an aqueous supplement of 3 mg Zn/d given without food increased plasma zinc (39).…”
Section: Figurementioning
confidence: 99%